Mechanical influence of tissue culture plates and extracellular matrix on mesenchymal stem cell behavior: A topical review. (March 2016) - Tatullo, Marco; Marrelli, Massimo; Falisi, Giovanni; Rastelli, Claudio; Palmieri, Francesca; Gargari, Marco; Zavan, Barbara; Paduano, Francesco; Benagiano, Vincenzo
Tissue engineering applications need a continuous development of new biomaterials able to generate an ideal cell–extracellular matrix interaction. The stem cell fate is regulated by several factors, such as growth factors or transcription factors. The most recent literature has reported several publications able to demonstrate that environmental factors also contribute to the regulation of stem cell behavior, leading to the opinion that the environment plays the major role in the cell differentiation. The interaction between mesenchymal stem cells (MSCs) and extracellular environment has been widely described, and it has a crucial role in regulating the cell phenotype. In our laboratory (Tecnologica Research Institute, Crotone, Italy), we have recently studied how several physical factors influence the distribution and the morphology of MSCs isolated from dental pulp, and how they are able to regulate stem cell differentiation. Mechanical and geometrical factors are only a small part of the environmental factors able to influence stem cell behavior, however, this influence should be properly known: in fact, this assumption must be clearly considered during those studies involving MSCs; furthermore, these interactions should be considered as an important bias that involves an high number of studies on the MSCs, since in worldwide laboratories the scientists mostly use tissue culture plates for their experiments.